Study of Dyes and Methods of Their Removal, with a Focus on Studying Their Removal using Photocatalysts Based on Polyoxometalates: Review - Jabbar, Wisam Abdalhusain; Jabbar, Marwa F. Abdul (Al-Nahrain Journal for Engineering Sciences, 2024)
Dyes are important chemicals in industrial uses; however, they are considered hazardous materials because they accompany sewage and are one of the causes of serious diseases such as cancer if not treated properly. The aim of this study is to specify the effect of dyes on the environment and human health and to remove them from water using the photochemical agent (polyoxometalate). By studying two types of Phosphotungstic acid (PTA) and phosphomolybdic acid (PMA) due to the good possibility of loading these acids on other materials using mixing and precipitation ways and without the need for high temperatures, as they are prepared at room temperature. They are also solid materials that are easy to separate, quickly dissolve in water, non-toxic, and do not release dangerous gases, which led to the need to use them in removing dyes, as they gave high efficiency. The research explains a comprehensive review of the use of PTA and PMA acid in Visible light-enhanced degradation of organic dye pollutants for three dyes: methylene blue, methyl orange and chromium B. Previous research is reviewed, with special emphasis on the performance of the photocatalyst, conditions that increase its efficiency, and the proposed mechanisms for the combined photocatalysts of PTA and PMA acids in developing the photocatalytic process. Finally, recent findings in this area are discussed, and possible future research continuations are suggested.